TRENDS AND CHALLENGES IN TEACHING PARAGRAPH WRITING: A COMPREHENSIVE LITERATURE REVIEW OF RECENT STUDIES (2025). - Erwin Kainta; Rahmatul Firdausa Umarella (Rahis Cendekia Indonesia, 2025)
Paragraph writing constitutes a crucial element in English language education, forming the foundation for developing coherent and logical written expression. Despite its importance, many learners continue to struggle with organizing their ideas, maintaining unity, and applying appropriate paragraph structures. To address these persistent issues, numerous scholars have examined innovative pedagogical approaches and the use of technology to enhance paragraph writing instruction. This study employs a Systematic Literature Review (SLR) method to identify current trends and challenges in teaching paragraph writing. A total of twenty-one research articles published in 2025 were selected from Google Scholar, following specific inclusion criteria related to paragraph writing in the field of English language education. The analysis followed three main procedures: identifying central themes, categorizing emerging trends and instructional challenges, and synthesizing findings through descriptive and thematic analysis. The results indicate a growing focus on integrating digital tools, applying process-based instruction, and emphasizing feedback-driven teaching practices. On the other hand, recurring challenges include students’ limited vocabulary, weak coherence, and teachers’ difficulties in adapting to technology-enhanced learning environments. The review concludes by offering pedagogical implications and proposing future research directions to enhance the effectiveness of paragraph writing pedagogy in EFL settings.